2022
DOI: 10.1152/ajpheart.00602.2021
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-mediated cutaneous microvascular function is not altered in young adults following mild-to-moderate SARS CoV-2 infection

Abstract: Vascular dysfunction has been reported in adults who have recovered from COVID-19. To date, no studies have investigated the underlying mechanisms of persistent COVID-19-associated vascular dysfunction. PURPOSE: To quantify nitric oxide (NO)-mediated vasodilation in healthy adults who have recovered from SARS-CoV-2 infection. We hypothesized that COVID-19-recovered adults would have impaired NO-mediated vasodilation compared to adults who have not had COVID-19. METHODS: We performed a cross-sectional study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
(74 reference statements)
1
20
0
2
Order By: Relevance
“…We ( 7 ) and others ( 5 , 13 ) have previously reported that brachial artery BP measured in the laboratory setting is not different between young adults who had COVID-19 and those who never had COVID-19. Although measuring BP in the laboratory setting is conventional and provides important information, it does not allow for the measurement of BP over an extended time period during regular daily activities, nor does it consider nocturnal dipping, the presence of whitecoat hypertension or masked hypertension.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We ( 7 ) and others ( 5 , 13 ) have previously reported that brachial artery BP measured in the laboratory setting is not different between young adults who had COVID-19 and those who never had COVID-19. Although measuring BP in the laboratory setting is conventional and provides important information, it does not allow for the measurement of BP over an extended time period during regular daily activities, nor does it consider nocturnal dipping, the presence of whitecoat hypertension or masked hypertension.…”
Section: Discussionmentioning
confidence: 70%
“…Central artery stiffness and central BP have also been shown to be higher within 3–4 wk from the COVID-19 diagnosis compared with controls ( 5 ). Findings from studies that included individuals further out from diagnosis suggests no elevation in arterial stiffness ( 7 ), and no impairment in vascular function ( 13 ) or impairment in only those with persistent symptoms ( 7 ). Although the temporal relationship between vascular dysfunction, elevated arterial stiffness, and elevated BP is a topic of some debate, it has been suggested that increased peripheral vascular resistance due to alterations in smaller arteries (i.e., impaired vasodilation and increased vasoconstriction) leads to elevated brachial BP, which causes greater large artery stiffness ( 30 , 31 ), followed by a rise in central BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective study also demonstrated that arterial hypertension following SARS-CoV-2 infection, either newly verified or worsened existing, was a relatively common occurrence [310] . However, some cross-sectional research showed that COVID-19 did not influence blood pressure, particularly in young subjects [311] , [312] , [313] , [314] . To resolve these discrepancies and clarify the pathophysiological effect on the BP of Long COVID, additional clinical and animal investigations are required, and exploring the mechanisms underlying cardiovascular manifestations among patients with Long COVID is warranted.…”
Section: The Role Of Counter-regulatory Ras To Link Hypertension and ...mentioning
confidence: 99%
“…According to Fignani et al, ( 91 ) β cells have high expression of ACE2 and lead to local cellular inflammation. Recent studies ( 85 ) demonstrated the high-dimensional approach to identify the subsequent consequences after SARS-CoV-2 infection impacted various organ systems via vascular dysfunction, nitric oxide-mediated microvascular function ( 92 ), contribution of von Willebrand factor ( 93 ) in thrombosis and inflammation ( 94 98 ), leading to respiratory, cardiovascular, gastrointestinal, neurological, cognitive, metabolic, and nephrological disorders along with anemia and general body aches, as well as general illness. The study of Al-Aly et al ( 85 ) also showed the use of various therapeutic agents including pain medications, antidepressants, antihypertensive, and oral hypoglycemic agents increasing the risk along with the evidence of laboratory abnormalities in several organ systems.…”
Section: Mechanism Of Sars-cov-2 Morbidity In Diabetesmentioning
confidence: 99%